A PHARMACODYNAMIC INTERACTIVE STUDY OF ATORVASTATIN AND GARLIC IN TREATMENT OF DYSLIPIDAEMIAS IN RATS. - G. DILIP REDDY; A. GOPALA REDDY (International Journal of Pharma and Bio Sciences, 2013)
This experiment was aimed to study the interaction between atorvastatin and garlic in correcting dyslipidaemias. A total of 56 male Sprague dawley rats were randomly divided into seven groups to evaluate the interaction of atorvastatin with garlic in induced dyslipidaemia. Different proportions of fresh garlic in feed and atorvastatin orally were fed in different groups for 12 weeks. Plasma was analyzed for total cholesterol, high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C) and triglycerides (TG) for every two weeks. All the treatment groups exhibited significant improvement in dyslipidaemic condition from 2nd week of treatment by reducing the TC, TG and LDL-C levels with subsequent increase in HDL-C levels. It can be concluded that garlic and atorvastatin exhibited positive pharmacodynamic interaction in reducing dyslipidaemias.